2023
DOI: 10.3390/ma16020851
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of End-Tapering Anchorages of EBR FRP-Strengthened Prestressed Concrete Slabs at Service Conditions

Abstract: This article examines numerically the behavior of prestressed reinforced concrete slabs strengthened with externally bonded reinforcement (EBR) consisting of fiber-reinforced polymer (FRP) sheets. The non-linear finite element (FE) program Abaqus® is used to model EBR FRP-strengthened prestressed concrete slabs tested previously in four-point bending. After the calibration of the computational models, a parametric study is then conducted to assess the influence of the FRP axial stiffness (thickness and modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Addition of AF in concrete mixes gradually reduces the workability properties, but addition of PR in optimized AF enhances the slump value of HSC mixes made with optimum dosages of AF (Figure 3). It is concluded that the production of HSC is possible with the addition of AF without compromising the workability properties of concrete, thereby adding the PR [29][30][31][32].…”
Section: Strength Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of AF in concrete mixes gradually reduces the workability properties, but addition of PR in optimized AF enhances the slump value of HSC mixes made with optimum dosages of AF (Figure 3). It is concluded that the production of HSC is possible with the addition of AF without compromising the workability properties of concrete, thereby adding the PR [29][30][31][32].…”
Section: Strength Propertiesmentioning
confidence: 99%
“…A tapering technique is proposed, gradually reducing FRP thickness towards the plate end, which reduces bond stress concentrations by up to 15% and prevents debonding. The study improves understanding of FRP-strengthened elements and advances computational tools for structural analysis [30]. Ortiz et al provide an overview of the environmental and mechanical factors affecting the durability and mechanical properties of fiber-reinforced polymer (FRP) composites used in reinforced concrete (RC) structures, highlighting the potential effects of harsh environmental conditions and mechanical phenomena on FRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, frequently considered the most important [14], can be classified [15] as intermediate shear-or flexural-induced debonding (related to the onset of intermediate cracks in high-tension regions, which propagate towards the strengthening end), plate end interfacial debonding [16,17] (related to the low adhesive bond strength of the adhesive layer at the concrete-FRP interface), and concrete cover separation [18] (related to adhesive interface layer bond strength significantly higher than concrete tensile strength). Moreover, in the literature, experimental and numerical works investigate the effects of the thickness or the elastic modulus of the FRP plate on the efficiency of the FRP plate bonding [19] and propose an analytical approach to determine the excessive deformation induced by the shear crack propagation [20], also providing retrofitting techniques based on the near-surface-mounted (NSM) carbon fiber-reinforced rod method, as reported in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the longer standing method of externally bonded laminates (EB-FRP) [9,10], this technique has some significant advantages, especially regarding better adhesiveness, which directly improves the mechanical characteristics of the strengthened beams [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%